Redução da evaporação em tanques de 20M2 por filmes monomoleculares de hexadecanol e suas influências na qualidade da água - Agostinho, Luewton Lemos Felício (2007)
Brazilian Northeast region, with its Semi-Arid conditions, has suffered difficulties due to its high evaporation levels. This evaporation brings great losses to the region and, in consequence, to the country. The present work studies one of the world most popular tools to control evaporation in open pans – hexadecanol monomolecular films - and the consequences of its application in water quality. It was used open pans of 20m2 of area (Russian Pans) built on Agrometeorological Station of Ceará University in Fortaleza. The experiments takes 3 years where were evaluated the film effectiveness, the statistical correlation between the evaporation reduction and the weather conditions, and the influence of the film application on biotic (phytoplankton, bacteria, fungus and fishes) and abiotic (turbidity, temperature, electrical conductivity, pH and salinity) characteristics of the water. It was also evaluated the dispersion velocity of the surfactant and the formation of “strings”. Results show that the product is able to reduce evaporation in 40% in Semi-Arid conditions. It was also presented that wind velocity and air temperature have some influence on evaporation reduction. Concerning the abiotic parameters the film application just causes significant alteration in water temperature. Phytoplankton and fishes does not suffer influences of the surfactante also, but it was notice some selectivity in fungus and bacteria species.